Breaking Boundaries: Discovering the Impossible Counterproof of Beal’s Conjecture - Mohamed, Halima Jibril; Zyfi, Adela; Futzum, Ghedlawit (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
This paper will attempt to logically differentiate between two types of fractions and discuss the idea of Zero as a neutral integer. This logic can then be followed to create a counterexample and a proof for Beal’s conjecture.